Prevalence of diarrheogenic Escherichia coli and rotavirus among children from Botucatu, São Paulo State, Brazil - Rodrigues, J. [UNESP] (2002)
In a one-year prospective study carried out to define the role of rotavirus and Escherichia coli in local childhood diarrhea, we determined the prevalence of both agents in 54 diarrheic children attending a health center in Botucatu. Diarrheogenic E. coli (DEC) strains were characterized by O:H serotyping, a search for virulence genetic markers, and assays of adherence to HEp-2 cells. Except for enteroaggregative E. coli (EAEC), no other DEC category was detected in the children's stools. Both EAEC and rotavirus were isolated from 22 of the 54 (41.0%) diarrheic children as single agents or in combination with other enteropathogens. However, when considering the presence of a single agent, EAEC was dominant and isolated from 20.4% of the patients, whereas rotavirus was detected in 14.8%. These results indicate that rotavirus and EAEC play a significant role as agents of childhood diarrhea in the local population.